Pengaruh Senam Prenatal Yoga terhadap Penurunan Kecemasan Ibu Hamil Trimester III - Ashari Ashari; Gabriellyn Sura Pongsibidang; Andi Mikhrunnisai (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
An anxiety is a feeling of worry associated with feelings of uncertainty or helplessness and an emotionalconditions that is not yet clear about its specific object. Anxious conditionsoccurs a lot in pregnant women whohave approached delivery period. This study aims to know influence of yoga prenatal gym to decreasing in anxietyof third trimester pregnant women in pattingalloang community health center and tamalate community healthcenter makassar city. the type of research used included quasi experiment with a design that is the nonrandomizedpretest posttest with control group design. This sample of study was 120 pregnant women that was divided 2groups, namely group I (intervention group) for 60 pregnant women and group II (control group) for 60 pregnantwomen. Data analysis was univariate and bivariate analysis. The results showed a significant relationshipbetween yoga prenatal gym intervention in reducing the incidence of anxiety in third trimester pregnant women inPattingalloang Health Center and Tamalate Health Center Makassar City with a value of p=0,000. Theconclusion of this study shows that yoga exercises at the prenatal stage have an influence on the decline in theincidence of anxiety of pregnant women.